2023
DOI: 10.1021/acsomega.2c07241
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a Superhydrophobic Surface by a One-Step Powder Pressing Method with Liquid Silicone Rubber As the Carrier

Abstract: The preparation methods of the superhydrophobic surface play an important role in its application, but most of the existing preparation methods are complicated in operation, high in cost, and polluting to the environment. In order to find a simple, rapid, lowcost, and nonenvironmentally polluting preparation method of the superhydrophobic surface, this paper used liquid silicone rubber as the carrier. Before the liquid silicone rubber was nearly cured, it was evenly covered with a layer of silicon dioxide powd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Various studies have shown that achieving a hydrophobic or superhydrophobic surface state, when the value of the water contact angle is more than 90 or 150 • , respectively, causes effects such as increasing the corrosion resistance of materials [1,2], enhancing heat exchange processes [3,4], reducing the hydraulic resistance during the transport of liquid media [5], reducing the rate of ice formation [6,7] and the formation of various types of deposits [8], and many others. Moreover, many studies claim that the degree of hydrophobicity has a direct influence on the magnitude of the above effects.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that achieving a hydrophobic or superhydrophobic surface state, when the value of the water contact angle is more than 90 or 150 • , respectively, causes effects such as increasing the corrosion resistance of materials [1,2], enhancing heat exchange processes [3,4], reducing the hydraulic resistance during the transport of liquid media [5], reducing the rate of ice formation [6,7] and the formation of various types of deposits [8], and many others. Moreover, many studies claim that the degree of hydrophobicity has a direct influence on the magnitude of the above effects.…”
Section: Introductionmentioning
confidence: 99%